Diameter and height distributions in a gallery forest tree community and some ofits main species in central Brazil over a six-year period (1985-1991) - Felfili, Jeanine Maria (1997)
The diameter and height structure were studied over six years in approximately 64 ha of the Gama gallery forest in Brasília, DF. Trees from 10 cm dbh were measured every three years from 1985 in 151 (10 x 20 m) permanent plots. Natural regeneration (individuals under 10 cm dbh) was measured in subplots within the 200 m2 plots. Most individuals and species were under 45 cm diameter and 20 m high while the maximum diameter for individual species ranged from 30 to 95 cm. The diameter structure was typical of a mixed tropical forest with the number of individuals decreasing with increasing size classes and showing little change over the six years. The most abundant species occupy different positions in the canopy and have different size structures. _______________________________________________________________________________ RESUMO